We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

Alice and Bob each have a certain amount of money. If Alice receives n dollars from Bob, then she will have 3 times as much money as Bob. If, on the other hand, she gives n dollars to Bob, then she will have 2 times as much money as Bob. If neither gives the other any money, what is the ratio of the amount of money Alice has to the amount Bob has?

By The Way.....

The answer 11/13 is WRONG

CPhill got this question wrong (rerember CPhill? it was only yesterday)

Sooo if you get this question correct you've finally solved a problem CPhill GOT WRONG!!!

Guest Oct 10, 2017

#1**+1 **

Hey, CPhill is just a human too! remember that!!

( Here is the original question. )

I think the two equations should be like this....

If Alice receives n dollars from Bob, then she will have 3 times as much money as Bob.

A + n = 3 * (B - n)

If she gives n dollars to Bob, then she will have 2 times as much money as Bob.

A - n = 2 * (B + n)

So we have..

A + n = 3B - 3n → A = 3B - 4n → 3A = 9B - 12n

A - n = 2B + 2n → A = 3B + 3n → 4A = 12B + 12n Add these two to get..

7A = 17B → 7A / B = 17 → A / B = 17 / 7

hectictar Oct 10, 2017

#1**+1 **

Best Answer

Hey, CPhill is just a human too! remember that!!

( Here is the original question. )

I think the two equations should be like this....

If Alice receives n dollars from Bob, then she will have 3 times as much money as Bob.

A + n = 3 * (B - n)

If she gives n dollars to Bob, then she will have 2 times as much money as Bob.

A - n = 2 * (B + n)

So we have..

A + n = 3B - 3n → A = 3B - 4n → 3A = 9B - 12n

A - n = 2B + 2n → A = 3B + 3n → 4A = 12B + 12n Add these two to get..

7A = 17B → 7A / B = 17 → A / B = 17 / 7

hectictar Oct 10, 2017